Clinical and Immunological Effects of p53-Targeting Vaccines - Zhou, Shan; Fan, Chunmei; Zeng, Zhaoyang; Young, Ken H.; Li, Yong (Frontiers in Cell and Developmental Biology, 2021)
Immunotherapy, including immune checkpoint blockade and chimeric antigen receptor T cells, is one of the most promising approaches to treat cancer. Vaccines have been effective in preventing cancers like liver cancer and cervical cancer with a viral etiology. Instead of preventing disease, therapeutic cancer vaccines mobilize the immune system to attack existing cancer. p53 is dysregulated in the majority of human cancers and is a highly promising target for cancer vaccines. Over twenty clinical trials have targeted p53 in malignant diseases using vaccines. In this work, we review the progress of vaccinations with p53 or its peptides as the antigens and summarize the clinical and immunological effects of p53-targeting vaccines from clinical trials. The delivery platforms include p53 peptides, viral vectors, and dendritic cells pulsed with short peptides or transduced by p53-encoding viruses. These studies shed light on the feasibility, safety, and clinical benefit of p53 vaccination in select groups of patients, implicating that p53-targeting vaccines warrant further investigations in experimental animals and human studies.